Reported transfusion‐related acute lung injury associated with solvent/detergent plasma – A case series. Issue 3 (17th February 2022) - Klanderman, Robert B.; Bulle, Esther B.; Heijnen, Josephine W. M.; Allen, Judith; Purmer, Ilse M.; Kerkhoffs, Jean‐Louis H.; Wiersum‐Osselton, Johanna C.; Vlaar, Alexander P. J.
Abstract: Background: Antibody‐mediated transfusion‐related acute lung injury (TRALI) is caused by donor HLA or HNA antibodies in plasma‐containing products. In the Netherlands 55, 000 units of solvent/detergent plasma (SDP), a pooled plasma product, are transfused yearly. It's produced by combining plasma from hundreds of donors, diluting harmful antibodies. Due to a lack of reported cases following implementation, some have labeled SDP as "TRALI safe". Study design and methods: Pulmonary transfusion reactions involving SDP reported to the Dutch national hemovigilance network in 2016–2019 were reviewed. Reporting hospitals were contacted for additional information, cases with TRALI and imputability definite, probable, or possible were included and informed consent was sought. Results: A total of three TRALI and nine TACO cases were reported involving SDP. The imputability of one TRALI case was revised from possible to unlikely and excluded; in one case no informed consent was obtained. We present a case description of TRALI following SDP transfusion in a 69‐year‐old male, 3 days following endovascular aortic aneurysm repair. The patient received one unit of SDP to correct a heparin‐induced coagulopathy, prior to removal of a spinal catheter post‐operatively. Within five hours he developed hypoxemic respiratory failure requiring intubation, hypotension, bilateral chest infiltrates, and leucopenia. The patient made a full recovery. Conclusion: This case of TRALI, following transfusion of a single unit of SDP to a patient without ARDS risk factors, demonstrates that TRALI can occur with this product. Clinicians should remain vigilant and continue to report suspected cases, to help further understanding of SDP‐associated TRALI.